Basis for choice of treatment of patients with fracture of the proximal humeral - B. E. Gurkin; A. S. Kalintsev; D. V. Ivanov (Кубанский научный медицинский вестник, 2015)
In the article reported the results of analysis of the treatment of 531 patients with fracture of the proximal humeral. As part of the study it was shown that using of the external osteosyntesis provides good results, which are not depend on bone mineral density. The results of the conservative treatment depend on premorbid condition of the osseous tissue. Whence external osteosyntesis is more convenient, the method of intramedullary fixation provides better results, and conservative treatment is reasonable for elder year class with normal bone mineral density.